Features of the personality adaptability of medical students in different courses of study - Yu. N. Timofeeva (Вестник университета)
The adaptability of personality of medical university students studying at different courses is investigated. Various approaches to the definition of the concept of personality adaptability are analysed, methods of its diagnosis are considered, the structure of the personal adaptability of medical students of all training courses is revealed. As a result of an empirical study it was revealed that the greatest deficiency in the structure of personality adaptability, characterized by a socio-oriented orientation, prevails in the first, second and fourth years. The adaptability of the personality of third-year students is in the zone of average values. Students of the fifth and sixth years of a medical university have the most harmoniously developed adaptability with the predominant characteristics of an autonomously oriented personality.